Forcing the system by a drift - S. Aliev; T. Gajiev; Ya. Rustamov; T. Maharramova (Математичні Студії)
We establish apriori estimate for the solutions of a degenerate non-divergence nonlinear elliptic equation. For this goal we study forcing the system by a drift.